A Short Review on Application of Fish Proteins in Functional Foods - Bikash Kumar Pati; Lalbiaknguri; Shreya Anand; Tanuja Kulshrestha; Anand Vaishnav; N. Sureshchandra Singh; Naresh Kumar Mehta; Bhargavi Priyadarshini; V. Alamelu (International Journal of Marine Life, 2024)
Functional foods contain specific nutrients that have beneficial physiological benefits, such as lowering the risk of chronic diseases and improving overall health. Functional foods are created by adding additives that have been shown to enhance health. This review article investigates several fish-derived products as functional dietary components, with an emphasis on fish protein hydrolysates (FPH), fish protein concentrate (FPC), fish collagen, fish gelatine, fish enzymes, fish protein powder (FPP) and surimi powder. Fish Protein Hydrolysates, produced from fish waste, are high in bioactive peptides and have unique nutritional value, making them useful in food manufacturing. Fish Protein Concentrate contains a high protein content and bioactive peptides with multiple health benefits, making it ideal for improving nutritional quality in an array of food products. Fish collagen, with its biocompatibility and versatile capabilities, is used to increase protein content and improve sensory attributes in food products. Fish gelatine, made by thermal denaturing collagen, is used for its gelling, viscosity, and emulsifying qualities, which improve the texture and stability of food items. Fish enzymes, due to their specific catalytic activity, enhance flavour, solubility, and nutritional value in a range of food processes. Fish Protein Powder, a stable and high-protein product, improves the nutritional value of ready-to-eat meals and snacks. Surimi powder, a dehydrated form of frozen surimi, is versatile in food formulations. The sustainable extraction and processing of fish proteins not only reduce waste but also offer promising avenues for functional food development. The future of fish protein in functional meals appears promising, with continuing research concentrating on sustainable extraction as well as processing methods. As consumer awareness of functional foods increases, so will the worldwide market, which is driven by the demand for nutrient-rich, health-promoting foods. To meet this need, producers must present convincing scientific proof for their health claims.
Keywords: Fish collagen; Fish protein; Fish protein concentrate; Fish protein hydrolysate; Fish protein powder; Surimi powder; functional food